Topological investigation of the ethanol/water system and its implications for the mode of action of homœopathic medicines - Singh, Prem P.; Chhabra, H.L. (British Homeopathic Journal, 1993)
Available molar excess volumes VE and molar excess enthalpies HE data at 250°C in the ethanol (E) and Water (W) system have been analysed in terms of a graphtheoretical approach to suggest that both E and W (in the pure state) exist as equilibrium mixture of various r-meric forms, that the particular configuration that they acquire in their mixture is dictated by their relative proportions. Although E undergoes hydrophobic interactions in W, specific interactions between E and W favour their mutual dissolution. The process of succussion (or trituration) of homœopathic drugs with E (or lactose) produces potentized E or W molecules that mimic the properties of the drugs. Homœopathic medicines have been postulated to operate via electron-transfer processes in the Central Nervous System. A mode of action of homœopathic medicines, consistent with the recent concepts of chemistry and physics is proposed to explain the scientific basis of the law of similars and some other characteristic pharmacologic actions of homœopathic medicines.
Keywords: Water; Ethanol; Topology; Physics; Mechanism of action